Combine harvester outsourcing services and seasonal rural non-farm employment in Myanmar - Belton, Ben; Fang, Peixun; Reardon, Thomas (Wiley, 2025)
Prior research on mechanization outsource services has not explored seasonal variations in drivers and outcomes of adoption by smallholders. These omissions are important because seasonality of crop cultivation may influence intensity of demand for machines, while seasonality of demand for non-farm labor may influence the availability and cost of agricultural workers and the opportunity costs of on-farm self-employment. We analyze seasonal correlates of combine harvester outsource service use in Myanmar. Surprisingly, adoption is not associated with lower labor costs or higher net margins from paddy cultivation. Rather, using combines releases family labor into more remunerative dry season non-farm employment.